Cosmopolitan conservation: the multi-scalar contributions of urban green infrastructure to biodiversity protection - Zbigniew Grabowski; Andrew J. Fairbairn; Leonardo H. Teixeira; Julia Micklewright; Elizaveta Fakirova; Emannuel Adeleke; Sebastian T. Meyer; Claudia Traidl-Hoffmann; Michael Schloter; Brigitte Helmreich (Biodiversity and Conservation, 2023)
Urbanization is a leading cause of biodiversity loss globally. Expanding cities alter regional ecological processes by consuming habitat and modifying biogeochemical and energetic flows. Densifying cities often lose valuable intra-urban green spaces. Despite these negative impacts, novel urban ecosystems can harbor high biodiversity and provide vital ecosystem services for urban residents. Recognizing the benefits of urban ecosystems, cities across the globe are increasingly planning for urban green infrastructure (UGI). UGI as a planning concept can transform how cities integrate biodiversity into urbanized landscapes at multiple scales and contribute to conservation goals. Full operationalization of UGI concepts can also reduce urban energy and resource demands via substituting polluting technologies by UGI, further contributing to the global conservation agenda. Realizing the potential contributions of UGI to local, regional, and global conservation goals requires addressing four inter-dependent challenges: (1) expanding social-ecological-systems thinking to include connections between complex social, ecological, and technological systems (SETS), (2) explicitly addressing multi-level governance challenges, (3) adapting SETS approaches to understand the contextual and biocultural factors shaping relationships between UGI and other causal processes in cities that shape biodiversity, and (4) operationalizing UGI systems through robust modeling and design approaches. By transforming UGI policy and research through SETS approaches to explicitly integrate biodiversity we can support global conservation challenges while improving human wellbeing in cities and beyond.